2020
DOI: 10.1111/ajco.13420
|View full text |Cite
|
Sign up to set email alerts
|

Trends in epidemiology, treatment and molecular testing of metastatic colorectal cancer in a real‐world multi‐institution cohort study

Abstract: Aim Colorectal cancer (CRC) is the third most common cancer in Australia, and survival after diagnosis of metastatic disease is improving. Our aim was to assess trends in epidemiology, treatment, molecular testing and survival in patients with metastatic CRC (mCRC). Methods Clinical data from February 2013 to December 2018 was recorded in a prospective, observational, multicenter cohort study conducted in Queensland, Australia, examining clinical and molecular biomarkers in cases of mCRC. Results A total of 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
(57 reference statements)
0
6
0
Order By: Relevance
“… 1 Metastases are present at diagnosis in 20 to 25% of cases, and for another 20 to 25% of patients, metastatic disease develops after initial surgical treatment. 2 , 3 For the majority of these patients, multiple organs are involved. 4 The liver is most commonly affected, followed by the peritoneum and lungs.…”
mentioning
confidence: 99%
“… 1 Metastases are present at diagnosis in 20 to 25% of cases, and for another 20 to 25% of patients, metastatic disease develops after initial surgical treatment. 2 , 3 For the majority of these patients, multiple organs are involved. 4 The liver is most commonly affected, followed by the peritoneum and lungs.…”
mentioning
confidence: 99%
“…Multivariate survival analyses using Cox proportional hazards models revealed that metastasectomy was signi cantly associated with increased survival in stage T1 colorectal cancer patients with synchronous distant metastasis. The metastasectomy in metastatic colorectal cancer demonstrated the survival bene cial in previous studies [34][35][36][37] . Simultaneous colorectal and minor hepatic resections are considered to be safe for most patients with synchronous liver metastases 38 .…”
Section: Serum Cea Status and Metastatic Sitesmentioning
confidence: 74%
“…Enterostomy, also known as artificial anus, is a section of intestinal opening artificially flipped and sewn to the abdominal wall incision after resection of the intestinal lesion to replace the function of the anus in order to solve the defecation problem of colorectal cancer patients [ 19 , 20 ]. However, enterostomy causes great inconvenience to patients' life, resulting in great physical and psychological pain, and even affects their compliance with subsequent treatment [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the current implementation of neoadjuvant therapy has reduced the recurrence rate of local lesions and increased the possibility of anus preservation, a considerable number of patients still have local recurrence due to the particularity of the physiological and anatomical location of the colorectal part and the lymphatic drainage pathway [17,18]. Enterostomy, also known as artificial anus, is a section of intestinal opening artificially flipped and sewn to the abdominal wall incision after resection of the intestinal lesion to replace the function of the anus in order to solve the defecation problem of colorectal cancer patients [19,20]. However, enterostomy causes great inconvenience to 3 Computational and Mathematical Methods in Medicine patients' life, resulting in great physical and psychological pain, and even affects their compliance with subsequent treatment [21].…”
Section: Discussionmentioning
confidence: 99%